Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acsomega.7b00912
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Silicon Pillar Arrays To Enhance Fluorescence Detection of Uranium and DNA

Abstract: There is an ever-growing need for detection methods that are both sensitive and efficient, such that reagent and sample consumption is minimized. Nanopillar arrays offer an attractive option to fill this need by virtue of their small scale in conjunction with their field enhancement intensity gains. This work investigates the use of nanopillar substrates for the detection of the uranyl ion and DNA, two analytes unalike but for their low quantum efficiencies combined with the need for high-throughput analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The latter is easy to form water-soluble uranyl ion (UO 2 2+ ) compounds. Uranium in water samples has been determined using various physicochemical methods, including inductively coupled plasma mass spectrometry (ICP-MS) [3], in some cases combined with ion chromatography [4] and radiation measurement techniques [5,6], and other analytical methods such as differential pulse polarography [7], neutron activation analysis [8], gas chromatography [9,10], as well as γ and α spectrum [11]. Although these methods have high sensitivity and favorable detection limits, their application requires costly equipment and lofty operating expenses.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is easy to form water-soluble uranyl ion (UO 2 2+ ) compounds. Uranium in water samples has been determined using various physicochemical methods, including inductively coupled plasma mass spectrometry (ICP-MS) [3], in some cases combined with ion chromatography [4] and radiation measurement techniques [5,6], and other analytical methods such as differential pulse polarography [7], neutron activation analysis [8], gas chromatography [9,10], as well as γ and α spectrum [11]. Although these methods have high sensitivity and favorable detection limits, their application requires costly equipment and lofty operating expenses.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the high-aspect-ratio geometry of pillar arrays provides a large surface area per unit substrate, ideally suitable for energy storage and chemical/biological sensors. Functionalized Si nanopillar arrays showed a strong luminescence sensitivity in detecting trace metal ions (e.g., uranyl ions) at a concentration less than 1 ppm 13 . Several research groups also demonstrated various Si nanopillar sensors, where a functionalized pillar surface (e.g., prostate-specific antigen, bio/chemical molecules) detects specific biochemical signals, which are converted to an electrical current 10 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, also improvements in packing quality have been realized, which led to the emergence of fully ordered pillar array columns wherein the particles are replaced by lithographically structured silicon pillars. , Microfabricated packings have the advantage that also the permeability can be easily reduced, due to the design freedom in pillar positioning and shape . This allows for a minimization of the separation impedance. , Our group and several other groups have developed a wide range of pillar array columns configurations and dedicated fabrication methods for several column substrates. Also monolithic columns are well appreciated for their high permeability but cannot compete with packed (and pillar array) columns in terms of plate height . The latter aspect has, however, somehow surprisingly, not impeded that large peak capacities have been demonstrated with (polymeric) monolithic columns using large molecules, due to the abrupt desorption behavior (related to the large solvent strength value S ) of, e.g., proteins and peptides in these columns.…”
mentioning
confidence: 99%